Answer:
Mg(s) + 2Ag^+(aq) ---->Mg^2+(aq) + 2Ag(s)
Step-by-step explanation:
The key to balancing redox reaction equations is this; ensure that the number of electrons lost in the oxidation half reaction equation is equal to the number of electrons gained in the reduction half reaction equation. The both half reaction equations can now be combined to give the overall reaction equation.
For the redox reaction under consideration;
Oxidation half equation;
Mg(s) ------> Mg^2+(aq) + 2e
Reduction half equation;
2Ag^+(aq) +2e ----> 2Ag(s)
Overall balanced redox reaction equation;
Mg(s) + 2Ag^+(aq) ---->Mg^2+(aq) + 2Ag(s)